Concurrent Tuberculous Meningoencephalitis and Anti-NMDAR Encephalitis: A Case Report - Xiaoli, Chen; Qun, Wang; Jing, Li; Huan, Yang; Si, Chen (Frontiers in Neurology, 2022)
Background: Cases of tuberculosis triggering the development of anti-N-methyl-D-aspartate receptor (NMDAR) autoimmune encephalitis (AIE) are scarce. Case Presentation: Herein, we report for the first time the case of a patient who developed anti-NMDAR encephalitis likely due to tuberculosis. The patient, a 33-year-old man, experienced weight loss in the previous 2 years, presented with acute headache, fever, cognitive deficits, and right ophthalmoplegia. Based on these findings along with magnetic resonance imaging and cerebrospinal fluid antibodies data, tuberculous meningoencephalitis and pleurisy combined with anti-NMDAR AIE was diagnosed. Marked clinical and brain imaging improvement were observed after antituberculosis and high-dose corticosteroid treatment initiation, which persisted during the 3 months of follow-up. Conclusions: This case suggests that anti-NMDAR AIE may arise after tuberculosis infection. Therefore, clinicians must be aware of this possibility, particularly if cognitive and/or new neurological symptoms suddenly occur.